Upper extremity entrapment neuropathies in patients with spinal cord injury - UZUN, Nurten; ULUDÜZ, Derya; RAHİMPANAH, Azar and KARAMEHMETOĞLU, Şafak Sahir (Cerrahpaşa Medical Journal, 2014)
Upper extremity entrapment neuropathies are more common in patients with spinal cord injury. The purpose of this study is to determine the presence and the prevalence of upper extremity entrapment neuropathies in patients with spinal cord injury. 31 patients (22 male, 9 female), who have spinal cord injury for more than 4 months, between the ages of 11 and 56 years (mean 32.8 ± 11.1) were enrolled. The patients were evaluated in regards to demographic, clinical and electrophysiological data. The parameters in patients with entrapment neuropathies were compared with the patients without entrapment neuropathy. Out of 31 patients studied, 9 had electrophysiologically Carpal Tunnel Syndrome (29 %). Disease duration was significantly longer in CTS patients (p=0.045). 5 patients showed median and 5 showed ulnar nerve pathology. Median nerve pathologies were Carpal Tunnel Syndrome in all patients. 3 had right (one in moderate sensorial fibers, one had severe sensorial and moderate motor nerve, last had moderate motor and sensorial nerve fiber pathologies), 1 had left (with severe motor and sensorial nerve fiber involvement) and 1 had bilateral (severe motor and sensorial nerve fibers involvement in right and moderate involvement in left side) Carpal Tunnel Syndrome findings. Among patients with ulnar nerve neuropathy, 2 had right (Type IV), 1 had left (Type IV) and 2 had bilateral pathologies. It is our belief that the high prevalence of Carpal Tunnel Syndrome in patients with spinal cord injury is the result of excessive use of their hands. This study documents the prevalence of entrapment neuropathies and emphasizes the need for early and periodic electrophysiological evaluations for prevention and early treatment for these syndromes.